2019
DOI: 10.1017/s1092852919001238
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ketamine in the management of anxiety and anxiety spectrum disorders: a review of the literature

Abstract: Anxiety disorders are among the most prevalent psychiatric conditions. Despite many proven pharmacological and non-pharmacological treatments available, high rates of partial response and low rates of long-term remission remain. Ketamine has been receiving increasing attention as an interventional treatment modality in psychiatry, especially among refractory conditions, including major depressive disorder. There is limited yet growing evidence to support the use of ketamine in anxiety disorders. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 69 publications
2
29
2
1
Order By: Relevance
“…In comparison, others [17] have found that increased spontaneous signal diversity in sub-anaesthetic ketamine was correlated with overall intensity of psychedelic experience as well as ego-dissolution and vivid imagination, which corresponds to the subscales disembodiment and complex imagery of the 11D-ASC. It is not clear why our results differ with previous studies, and why anxiety would have a positive, significant correlation with signal diversity, although there is some evidence that ketamine may be useful for treatment of depression and anxiety disorders [49]. Further investigations are probably needed to further test and clarify the reasons for these apparent correlations.…”
Section: Relating Signal Diversity To Phenomenological Changescontrasting
confidence: 89%
“…In comparison, others [17] have found that increased spontaneous signal diversity in sub-anaesthetic ketamine was correlated with overall intensity of psychedelic experience as well as ego-dissolution and vivid imagination, which corresponds to the subscales disembodiment and complex imagery of the 11D-ASC. It is not clear why our results differ with previous studies, and why anxiety would have a positive, significant correlation with signal diversity, although there is some evidence that ketamine may be useful for treatment of depression and anxiety disorders [49]. Further investigations are probably needed to further test and clarify the reasons for these apparent correlations.…”
Section: Relating Signal Diversity To Phenomenological Changescontrasting
confidence: 89%
“…More recently, ketamine has also begun to be studied in anxiety disorders (130). One small open-label trial looking at the efficacy of ketamine in treatment-refractory generalized anxiety and/or social anxiety disorders (104) found that ten out of twelve patients responded (i.e., achieved ≥50% reduction in HAM-A scores and/or Fear Questionnaire scores) after three ascending doses of once weekly subcutaneous ketamine (0.25, 0.5, and 1 mg/kg); a subsequent trial from the same group further supported the safety and efficacy of ketamine (1 mg/kg) for this same population with once or twice weekly subcutaneous administrations over a period of three months (131).…”
Section: Pharmacological Agents Targeting Glutamate Neurotransmissionmentioning
confidence: 99%
“…Here, we present data for the analgesic and cardiovascular effects of low dose ketamine, a non-opioid based analgesic, that may be considered to reduce opioid medication overuse and abuse. Lastly, the effects of low-dose ketamine on cardiovascular regulation demonstrated herein may also inform off-label clinical use to treat other disorders such as major depressive disorders (Domany et al 2019), anxiety disorders (Banov et al 2019) and migraine pain (Lauritsen et al 2016).…”
Section: Discussionmentioning
confidence: 88%
“…2017; Banov et al . 2019) would have reduced sympathetic and cardiovascular responses during the CPT, given that anticipation and anxiety are known to influence pain perception (Burgmer et al . 2011).…”
Section: Discussionmentioning
confidence: 99%